Conservative Management of Left Ventricular Thrombus Patient with Decreased Systolic Function: A Case Report - I Kadek Herry Hermawan; Ken Christian Kawilarang; Febriyanti Hartono (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlights: It provides insight into the management of LVT. Abstract: Case Summary. A 35-year-old male complained shortness of breath for 1 month, had worsened in the last 3 days. When walking 3-5 steps, the patient already felt dyspneu. When sleeping, the patient must be in a semi-sitting position, and sometimes still feels tight. The patient also complained of occasional chest pain. The patient is known to have a history of heart disease, and a history of taking drugs such as candesartan, ISDN and bisoprolol. Discussion. Left ventricular thrombus (LVT) is a frequent and potentially dangerous complication of acute myocardial infarction and is associated with increased risk of systemic embolization. Incidence of LVT following acute MI has decreased, probably due to improvement in patient care as a result of better and earlier reperfusion techniques. Management of LVT is primarily based on studies before the widespread use of potent pharmacological and interventional therapies such as primary percutaneous coronary intervention, especially in the setting of acute myocardial infarction. Though advances in diagnostic technology have improved detection of LVT, clinicians face several uncertainties in the management of LVT in daily practice.